Thermodynamic modeling of absorption heat pumps - Jarlros, Helen (My University, 2010)
In order to recover as much as possible of the energy released in the waste incineration process at Renova, six lithium bromide absorption heat pumps are utilized to raise the temperature of a recovered low temperature stream. The recovered heat utilized in the absorption heat pumps comes from the flue gas cleaning process, and is after the temperature has been raised in the heat pumps, delivered to the district heating network. Four of the six heat pumps is of an older brand called Sanyo and has nominal effect of 4MW each. The two more modern heat pumps have a nominal effect of 6MW and are of brand called Entropie. As a part of an energy optimization project initiated at Renova, together with a consultant company called “Energy project E&S”, the entire plant, including the absorption heat pumps, have been represented in an Excel based model (here referred to as Model-Renova). This model started with simple equations describing a small part of the energy recovery process and the choice to use Excel as a base for the modeling, was explained by the simplicity of Excel and the fact that Excel is a common and well known program, The aim of this model is to find the optimal process solutions that would result in a more optimal use of the energy released in the combustion. The parts of the Model-Renova that represents the absorption heat pumps are based on empirical correlations formulated from collected process data and represent the six heat pumps as two units. The Model-Renova has an unknown range of validity, accuracy and a limited possibility to model the individual heat pumps. The accuracy of this heat pump model was evaluated by comparing the result of this model with real process data. The old model has a fairly god accuracy in predicting the district heating temperature, but give slightly over or under predicted estimations of the heat recovered by the heat pumps and the coefficient of performance. However a possibility to improve the model by changes in the governing equations could improve the accuracy. This master’s thesis work focus on creating an improved model (New-model) of these heat pumps with a better defined range of validity and the possibility to individualize the model to each separate heat pump. Some theoretical background concerning the heat transfer and the absorption heat pumps is briefly presented in this report as a base for new models of the absorption heat pump. Energy and mass balances along with common calculation methods used in calculation with heat exchangers (the NTU method and the logarithmic mean temperature method) were used in the representation of the absorption heat pumps as an excel base models (New model ). The two brands of heat pumps (Entropie and Sanyo) were modeled in two separate theoretical models based on their design. These models should then be adapted to the six real heat pumps by altering a factor on the heat transfer coefficient. Due to some problems and difficulty in the modeling and the use of Excel as a modeling tool descried in the report, only one of the two types of heat pumps was completely modeled. It could also be concluded that the Model-Renova could, after some smaller alterations, be a fairly god representation of the real heat pumps from a process perspective.
Keywords: Kemiska processer; Chemical Process Engineering